2003
DOI: 10.1046/j.0001-6772.2003.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal and vascular oxidative stress and salt‐sensitivity of arterial pressure

Abstract: Oxidative stress occurs in a tissue or in the whole body when the total oxidant production exceeds the antioxidant capacity. Recent studies in human essential hypertension indicate that free radical production is increased and antioxidant levels are decreased, and more than one-half of these hypertensives have a salt-sensitive type of hypertension with progressive renal damage. Increased oxidative stress may also play a critical role in animal models of salt-sensitive hypertension. The stroke-prone spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 34 publications
8
89
0
Order By: Relevance
“…The pathophysiologic mechanisms underlying the development and maintenance of DOCA-salt hypertension include increased levels of arginine vasopressin [120], angiotensin-II/aldosterone [300,313], endothelin [179,204,258,302] and oxidative stress [154,175], excessive activation of the sympathetic nervous system [132] and nitric oxide synthase (NOS) uncoupling due to oxidative depletion of its cofactor tetrahydrobiopterin (BH4) [274]. Indeed, both inhibition of the angiotensin-aldosterone system and endothelin receptor blockade have been shown to prevent cardiac remodeling, even without concomitantly reducing arterial blood pressure [89,257].…”
Section: Doca-salt Ratsmentioning
confidence: 99%
“…The pathophysiologic mechanisms underlying the development and maintenance of DOCA-salt hypertension include increased levels of arginine vasopressin [120], angiotensin-II/aldosterone [300,313], endothelin [179,204,258,302] and oxidative stress [154,175], excessive activation of the sympathetic nervous system [132] and nitric oxide synthase (NOS) uncoupling due to oxidative depletion of its cofactor tetrahydrobiopterin (BH4) [274]. Indeed, both inhibition of the angiotensin-aldosterone system and endothelin receptor blockade have been shown to prevent cardiac remodeling, even without concomitantly reducing arterial blood pressure [89,257].…”
Section: Doca-salt Ratsmentioning
confidence: 99%
“…27,28 Kidney damage in DOCA-salt rats is accompanied by a significant increase in the production of reactive oxygen species, proinflammatory cytokines and profibrotic factors. 29 In this study, we investigated the renoprotective effects of cilnidipine in DOCA-salt rats and compared the effects with those of amlodipine. In addition, we also examined the effects of cilnidipine on the renal renin-angiotensin-aldosterone system.…”
Section: Introductionmentioning
confidence: 99%
“…3,13,14 A variety of evidence suggests that reactive oxygen species contribute to impaired endothelial function in several forms of hypertension and that there is increased oxidative stress in the microvessels of spontaneously hypertensive rats and Dahl salt-sensitive hypertensive rats. [15][16][17] A recent report by Lenda et al 7 has suggested that reactive oxygen species can also contribute to a reduced endothelium-dependent dilation in normotensive rats on a high-salt diet. Despite the potential importance of reactive oxygen species in contributing to impaired endothelium-dependent vasodilation and reduced NO production during elevated dietary salt intake, the nature and mechanisms of the impaired vascular relaxation with the high-salt diet and the role of enhanced oxidative stress in contributing to salt-induced changes in vascular function and hypertension are not completely understood.…”
mentioning
confidence: 99%